Semiotics on the Representation of Healthy Skin Beauty in Somethinc’s Instagram Posts - Amanda Sintyaningrum; ABD Hannan EF; R Myrna Nur Sakinah (Universitas Pahlawan Tuanku Tambusai, 2026)
As skincare has become increasingly integrated into contemporary beauty culture, cosmetic brands have actively promoted healthy skin as a primary indicator of beauty through social media platforms. Despite the widespread influence of these campaigns, limited studies have explored how beauty myths are constructed through skincare advertising on Instagram. This study aims to examine the representation of healthy skin in Somethinc’s Instagram posts and identify the beauty myths embedded within those representations. A qualitative research design was employed using Roland Barthes’ semiotic framework, which analyzes signs through the levels of denotation, connotation, and myth. The data consisted of five image-based Instagram posts published on Somethinc’s official account in 2025, selected through purposive sampling. The findings reveal that healthy skin is represented through themes of gentle care and pH balance, deep hydration and plumpness, the reduction of skin imperfections and renewal, youthfulness and regeneration, and barrier protection and recovery. These representations collectively construct beauty myths that position healthy skin as an idealized standard of attractiveness while portraying skincare routines as essential practices for achieving, maintaining, and legitimizing this culturally desirable beauty ideal.